Effect of Storage on Flavour, Colour and Other Sensory Qualities Of Sugarcane Juice (Saccharum Officinarum) Yellow Cane - Mahmoud Al-Hasan, Khaleel Abdul Fattah (2000)
A study was conducted to determine the effects of storage on the flavour and sensory attributes of sugarcane juice. Freshly extracted sugarcane juice was stored at 25 ± 20C and 5 ± 20C for IS-days. The parameters measured were colour, acidity (pH and TA), acidic phenolics and flavour. The sensory attributes tested were colour, viscosity, sweetness, sharpness, appearance, jaggery and fresh flavour. Phenolic compounds were separated using solid phase extraction technique and HPLC method was used for isolation and identification. Major volatiles were extracted using vacu um steam distillation (VSD) technique. Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS) were used for separation of the volatiles and identification of their molecular weights. Results indicated that sugarcane juice stored at 5 ± 20C retained its colour and acidity until 10-days meanwhile, a drastic change occurred on the colour and acidity of juice stored at 25 ± 2oC. The sensory results showed that no remarkable changes occurred on the quality (colour, viscosity, sweetness, sharpness, appearance,jaggery and fresh flavour) of samples stored at 5 ± 2°C up to 10- days. There were no significant differences (P>0.05) observed between samples stored for 5 and 10-days. However, at the end of the IS-days, there were significant differences (P<0.05) in terms of colour, sweetness, sharpness, jaggery and freshness compared to the fresh, the 5 and the 10-days stored juices (except for appearance and viscosity). Six types of phenolic compounds were identified in sugarcane juice namely 3,4-dihydroxybenzoic, chlorogenic, p-hydroxybenzoic, caffeic, p-coumaric and 2 ,3-dihydroxybenzoic acids. Changes in the phenolics contents were observed in samples stored at both temperatures (5 ± 2°C and 25 ± 2°C). Changes in the phenolics' concentrations were more noticeable in the juice stored at 25 ± 2°C. This occurred despite the fact that the polyphenol oxidase (PPO) was deactivated at the beginning before juice extraction. At the same time, there seemed to be increases and decreases in their concentrations. This may indicate that not only enzymatic reaction, which consumed the phenolics but also autoxidation reaction, may have occurred. Sugarcane juice was found to consist of about 17 major volatile compounds. Upon storage at 5 ± 2°C the major volatiles were retained until 10-days; after that some compounds were lost and others were evolved. After two days of storage at 25 ± 2°C the major volatiles were lost and many other new compounds were evolved.A strong relationship (R²≥0.90) was observed between some of the phenolics and the sensory attributes (colour, appearance, viscosity, sweetness, sharpness, jaggery and fresh flavour) . The changes in colour (ϪE) was also correlated well (R²=0.90) with the sensory evaluation results.In general, sugarcane juice stored at 5 ± 2°C retained its quality until l0-days. However, undesirable colour, flavour and the change in taste from sweet to sour occurred after the end of the I5-days at 5 ± 2°C. Significant changes in acidity, colour, flavour and phenolics were observed at 25 ± 2°C compared to 5 ± 2°C. In fact, the flavour of the sample stored at 25 ± 2°C changed significantly after 2 days. This indicated that the juice will lose its quality if kept at 25 ± 2°C and deterioration of the juice stored at 5 ± 2°C was only noticeable after the end of the 15-days.